Uneven treatment of family life? Horizontal equity in the U.S. tax and transfer system - Timm Bönke; Sebastian Eichfelder; Stephen Utz (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
We analyze the distributive justice of the combined burden of income taxes, social security taxes and public transfers on employee households in the United States on the federal level and in six member states. To investigate whether the treatment of families by the aggregate tax and transfer system can be regarded as fair, we compare the equivalent incomes of eight different household types. Using the concepts of horizontal equity and system-inherent equivalence scales, we find evidence for a privileged treatment of families with children and a low market income due to the earned income tax credit (EIC), the child tax credit and the supplemental nutrition assistance program (SNAP). If employment taxes are interpreted as taxes in the proper sense, we obtain a favorable treatment of family households and especially married couples for middle-sized market incomes. For high market incomes, we observe a decreasing privilege for all family types. Regarding state tax and transfer systems, temporary aid for needy families (TANF) substantially increases the observed privilege for low-income families compared to singles, while the analyzed state income taxes are generally in line with the federal tax scheme. Overall, our results imply a significant contradiction in value judgments within the U.S. tax and transfer system.
Keywords: D31; D63; H24; 330; horizontal equity; family taxation; distributive justice; tax and transfer system; equivalent income; equivalent income taxation